Meningkatkan Kapasitas Menurunkan Kerentanan Kunci Sukses Mitigasi Bencana Penanggulangan Krisis Kesehatan Bencana Erupsi Gunung Kelud - Tintin Hariyani; Dwi Ertiana; Brivian Florentis Yustanta; Rofiul Adauwiyah; Rizki Ananda Eka (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Indonesia is prone to natural disasters because it is located at the confluence of three active tectonic plates. This condition causes high earthquake, volcano, and tsunami activity in Indonesia. Mount Kelud is the most active volcano in Indonesia with cycles that recur every 8 to 15 years. The community service method carried out is to collect data on the area, population, targets, capacity, vulnerability level, and empirical data on the 2014 eruption of Mount Kelud. Then conduct analysis, calculate estimates of health logistics needs, especially reproductive health, socialize the results of the analysis, and conduct disaster preparedness education. This activity was carried out for 6 weeks from March 12 to April 21, 2025. Based on the results of the risk assessment, the Ngancar District, Kediri Regency area has a score of frequent risk scale, severe impact scale, and priority and impact scale in the high category. To overcome the health crisis, a contingency plan is needed, especially for the reproductive health sub-cluster, which includes the preparedness of target data, existing capacity in the region, the level of vulnerability, and the estimated amount of health logistics needed to anticipate the eruption of Mount Kelud. Mount Kelud has a periodic eruption pattern in 8 to 15 years. The contingency plan for dealing with the health crisis of the eruption of Mount Kelud is very important for health service stakeholders because it can minimize the adverse impacts caused, increase rapid response, and ensure smooth coordination between related institutions in dealing with the natural disaster effectively and efficiently. It also supports disaster risk reduction efforts at the community level and strengthens the resilience of local communities.